Monocyte chemoattractant protein 1 (MCP-1) in temporal arteritis and polymyalgia rheumatica. Issue 10 (1st October 2000) - Ellingsen, T; Elling, P; Olson, A; Elling, H; Baandrup, U; Matsushima, K; Deleuran, B; Stengaard-Pedersen, K
Abstract : OBJECTIVE: To examine the localisation of monocyte chemoattractant protein 1 (MCP-1) in the inflamed vessel wall in temporal arteritis (TA) and to measure MCP-1 in plasma both in patients with TA and patients with polymyalgia rheumatica (PMR). METHODS: By immunohistochemical techniques MCP-1 was localised to the vessel wall in patients with TA. In TA, PMR, and healthy controls MCP-1 was quantified by enzyme linked immunosorbent assay (ELISA) in plasma. RESULTS: MCP-1 was localised to the majority of mononuclear cells, some smooth muscle cells, and giant cells in the arterial biopsy specimens from 12 patients with histologically verified TA. In all sections, including the vasa vasorum, the endothelium stained positive. In the intima 73% (range 57–91%), in the media 49% (range 32–67%), and in the adventitia 74% (range of 62–91%) of all cells stained positive. In plasma MCP-1 was significantly raised in untreated TA (n=33) and untreated PMR (n=27) compared with healthy controls (n=12). Untreated TA plasma levels of MCP-1 (mean 391 pg/ml (range 82–778 pg/ml)) were similar to untreated PMR plasma levels (mean 402 pg/ml (range 29–1153 pg/ml)), and no significant difference was found between the two groups of patients. In both patients with TA and patients with PMR no correlation was found between the plasma level of MCP-1 and the erythrocyte sedimentation rate, haemoglobin concentration, and CD4/CD8 ratio. CONCLUSIONS: These results show that MCP-1 plays a part in the disease processes of TA and PMR.